The complete chloroplast genome sequence of Hemerocallis fulva - Yan Zheng; Jingling Li; Haimei Chen; Linfang Huang (Mitochondrial DNA. Part B. Resources, 2020)
Hemerocallis fulva L. is a traditional Chinese medicine. The flowers of H. fulva are used in ethnic medicine to treat various diseases, including certain central nervous system diseases. In this study, we characterized the complete chloroplast genome of H. fulva. It is 156,059 bp in length and encodes 87 protein-coding genes, 38 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. The phylogenomic analysis showed that the H. fulva and species of Anemarrhena asphodeloides Bunge, Liriope muscari, and Liriope spicata were clustered together. This chloroplast genome sequencing offers genetic background for conservation and phylogenetic studies.